2014
DOI: 10.1193/100512eqs298m
|View full text |Cite
|
Sign up to set email alerts
|

Damping Scaling Factors for Elastic Response Spectra for Shallow Crustal Earthquakes in Active Tectonic Regions: “Average” Horizontal Component

Abstract: Ground motion prediction equations (GMPEs) for elastic response spectra are typically developed at a 5% viscous damping ratio. In reality, however, structural and nonstructural systems can have other damping ratios. This paper develops a new model for a damping scaling factor ( DSF) that can be used to adjust the 5% damped spectral ordinates predicted by a GMPE for damping ratios between 0.5% to 30%. The model is developed based on empirical data from worldwide shallow crustal earthquakes in active tectonic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(106 citation statements)
references
References 29 publications
(72 reference statements)
6
100
0
Order By: Relevance
“…The validity of the resulting model for longer distances was examined by residual analysis of the remainder of records. We observed that the general trends seen between DSF V and potential predictor variables-damping ratio, spectral period, duration, magnitude, distance, and site conditions-are similar to what was observed in Rezaeian et al (2014) for the horizontal component scaling factor, DSF H . Damping ratio was directly included in the model as a predictor variable.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The validity of the resulting model for longer distances was examined by residual analysis of the remainder of records. We observed that the general trends seen between DSF V and potential predictor variables-damping ratio, spectral period, duration, magnitude, distance, and site conditions-are similar to what was observed in Rezaeian et al (2014) for the horizontal component scaling factor, DSF H . Damping ratio was directly included in the model as a predictor variable.…”
Section: Discussionsupporting
confidence: 81%
“…The DSF was used to scale pseudo-response spectral accelerations (PSA) at a 5% damping ratio to PSA at other damping ratios. The "average" horizontal component, which hereafter will simply be referred to as the horizontal component, was represented in two ways: (1) GMRotI50 horizontal component, as defined by An alternative approach taken by most researchers, dating back to the classic work of Newmark and Hall (1982) and also used in Rezaeian et al (2014), is to develop models of multiplicative factors (i.e., DSF) that scale the 5% damped spectral ordinates predicted by any GMPE to ordinates for other damping ratios. The advantages of this approach are that it does not require interpolation between discrete damping ratios and can be easily applied to GMPEs other than those from which the model was derived.…”
Section: Damping Scaling Of the Vertical Response Spectrummentioning
confidence: 99%
“…The values of DRF have been plotted as a function of period at various levels of damping in Fig 6 . The DRF values tend to become unity at lower and higher periods because the forces in a very stiff or very flexible structure are relatively independent of the damping ratio [ 1 ]. This trend is observed in the DRF derived from the PSA irrespective of period and damping.…”
Section: Predictor Variables Usedmentioning
confidence: 99%
“…Most ground-motion prediction equations are available for a reference damping of 5%. The damping ratio depends on the structure, type of material, and ground shaking, among other characteristics [ 1 ]. In reality, however, structural systems may have a damping ratio other than 5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation